The research on environmental geophysics under climate change: Key frontiers and multidimensional development pathways - Wang, Zhijian; Zhao, Wenlei; He, Xinxin (Resources Data Journal, 2025)
As one of the most pressing global scientific and policy challenges today, climate change is profoundly affecting the stability and sustainable development of the Earth system. As a vital branch of Earth system science, environmental geophysics provides robust technical and theoretical support for identifying the driving mechanisms, feedback processes, and ecological and societal impacts of climate change through multi-source geophysical detection and monitoring technologies. This paper systematically reviews six key application areas of environmental geophysics in climate change research: glacial seismology, marine seismology, monitoring of polar and marine environments, assessment of greenhouse gas concentrations and emissions, evaluation of carbon capture and storage technologies, and climate system modeling. The research indicates that advanced technologies such as high-resolution seismic arrays, satellite remote sensing, ocean-bottom seismometers, and drone-based sensors enable refined monitoring and quantitative simulation of ice sheet melting, sea-level rise, greenhouse gas emissions, and subsurface carbon sequestration processes. Moreover, the deep integration of artificial intelligence and machine learning methods into geophysical data processing and climate system modeling has significantly enhanced the resolution and accuracy of climate predictions. Environmental geophysics is expected to play an increasingly strategic role in deepening our understanding of climate processes, improving climate risk assessment, optimizing global response strategies, and supporting the construction of climate governance systems.